A global theory of justice for new governance : from process to substance with 'parity of participation' - Hermann, Martin (2014)
This thesis proposes a new counter-narrative to the neo-liberal agenda that combines two seemingly disparate bodies of work: New Governance and Nancy Fraser’s theory of justice. New Governance is a new and rapidly growing strand of legal thought and practi ce that has simultaneously developed a following in Europe and the United States. In short, legal scholars in this field of research are advocating a shift away from long-standing command-style, fixed-rule regulation toward more collaborative, bottom-up, and flexible modes of regulation.
Law
Keywords: FRASER; Nancy; neoliberal hegemony; new governance